Efektivitas Pendidikan Pernikahan Dalam Membangun Keharmonisan Rumah Tangga - Ad-Da'i Ilal Haq, Moch. Abduh; Billah, Ana (Universitas Muhammadiyah Surabaya, 2024)
This research aims to deeply understand how the family, as the smallest unit in society, strives to create a harmonious and prosperous domestic life. A qualitative approach with phenomenological methods is used to explore individual life experiences in the context of family life. The data in this study were collected through three main ways: direct observation, in-depth interviews, and document studies. Qualitative data analysis will be used to describe in depth and comprehensively the findings obtained. Based on the results of the research, it can be concluded that the implementation of pre-marital marriage guidance at KUA Kademangan has met the established operational standards. The effectiveness of this program can be seen from the smooth running of activities, the availability of facilities and infrastructure, and its contribution to the readiness of the bride-to-be. Marriage guidance programs have proven to be effective in increasing the readiness of brides-to-be, both from